The lightning thief - Riordan, Rick. (New York : Miramax Books, 2005)
After learning that he is the son of a mortal woman and Poseidon, god of the sea, twelve-year-old Percy is sent to a summer camp for demigods like himself, and joins his new friends on a quest to prevent a war between the gods.
Keywords: Mythology, Greek; Mythology, Greek; Camps; Friendship; Fathers and sons; Poseidon (Greek deity)